The bran and the flour. Relevance of Philippe Gauthier’s thought on metics (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
In the pages that P. Gauthier dedicates to the metics in Symbola, his 1972 volume concerning foreigners and justice in the Greek world, several interesting aspects emerge regarding the figure of the resident foreigner, which are still debated today. This paper aims to retrace Gauthier’s thought on this aspect and to read it in the light of the scientific debate of the following fifty years. What emerges is a vision that in some respects deserves to be supplemented and updated, but in many others retains its vivid relevance. Gauthier, in contrast to many of the studies of recent decades, convincingly argues that the legal status of the metic is an indispensable component in determining his level of integration within the polis.
Keywords: Philippe Gauthier; greek law; integration; metic; prostates